2017
DOI: 10.3390/nano7110405
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Functions of Archimedes’ Spiral Metallic Nanostructures

Abstract: Here, we have reviewed some typical plasmonic structures based on Archimedes’ spiral (AS) architectures, which can produce polarization-sensitive focusing phenomenon and generate plasmonic vortices (PVs) carrying controllable orbital angular momentum (OAM) because of the relation between the incident polarized states and the chiralities of the spiral structures. These features can be used to analyze different circular polarization states, which has been one of the rapidly developing researching topics in nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…The mechanism for the optical fields is slightly different to the vortex formation of SPP on metallic surfaces. For the SPPs the grooves in the surface act as a source of SPPs and the vortex formation can be described by an interference pattern of waves running inside the spiral with the correct phase [2,3,5,7]. A similar equation for the vortex number has also been found [2,4,6,11,24,46].…”
Section: Mircometer-sized Spiralmentioning
confidence: 82%
See 2 more Smart Citations
“…The mechanism for the optical fields is slightly different to the vortex formation of SPP on metallic surfaces. For the SPPs the grooves in the surface act as a source of SPPs and the vortex formation can be described by an interference pattern of waves running inside the spiral with the correct phase [2,3,5,7]. A similar equation for the vortex number has also been found [2,4,6,11,24,46].…”
Section: Mircometer-sized Spiralmentioning
confidence: 82%
“…For the grooved spiral in a metal system, it was found that a vortex of SPPs is generated, when the distance d between the parts of the segmented spiral agrees with the wavelength of the propagating SPP [2,7,8].…”
Section: Mircometer-sized Spiralmentioning
confidence: 99%
See 1 more Smart Citation
“…Till now, several methods have been advanced to generate plasmonic vortex and they include single spiral nanoslit [9][10][11][12][13], spiral nanoslit with multiple arms [14][15][16][17], and distributed nanoholes [18][19][20]. Spiral slit has the advantages of simple structure, convenient manufacture and easy operation, and it is often used to generate low order optical vortex [21,22]. Spiral nanoslit with multiple arms is often used to generate high order optical vortex, where the small gap between the start to the end of each spiral can mitigate the influence of the SPP decay.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been applied to create optical active plasmonic nanostructures, including the direct synthesis or postsynthetic modification of metal nanoparticles, chiral assembly, or a range of various deposition techniques. Most of these approaches are restricted by using demanding experimental procedures, insufficient chirality, or a small area of resulted structures. Therefore, numerous approaches to prepare chiral plasmonic nanostructures reproducibly and in large-scale production have appeared recently. One of the promising methods utilizes the combination of intrinsically nonchiral plasmonic nanostructures with the chiral dielectric medium assuming the transfer of chiral response from the surrounding medium to plasmonic nanostructures. In this respect, a number of chiral biomolecules, including peptides, DNA, or aminoacids, were used as such chiral media.…”
Section: Introductionmentioning
confidence: 99%